Credit Risk, Operational Efficiency, and Profitability in Collateral-Based Lending: Evidence from Indonesia’s State-Owned Pawnshop - Fitria Ayu Lestari Niu; Fanda Daisy Prully Rundengan; Priscilia Christina Sumendap (Academic Bright Collaboration, 2026)
Purpose – Credit risk, operational efficiency, and profitability have been extensively studied in banking, yet evidence from collateral-based non-bank financial institutions remains limited. This study examines the effect of credit risk (NPL) and operational efficiency (BOPO) on profitability (ROE) at PT Pegadaian, the largest state-owned pawnshop in Indonesia. Methods – A quantitative approach is employed using 18 quarterly observations drawn from PT. Pegadaian’s published financial statements for the period Q3 2021-Q4 2025. The analysis applies multiple linear regression, with classical assumption tests, and hypothesis testing employs the T-test (partial) and the F-test (simultaneous). Findings – Credit risk has a significant negative effect on profitability, consistent with risk management theory. Operational efficiency does not significantly affect profitability, which contradicts predictions from efficiency theory. Simultaneously, both variables significantly affect profitability. The model yields an adjusted R-square of 28.4%, indicating that 71.6% of ROE variation is attributable to factors outside the model, including macroeconomic conditions, gold prices, capital adequacy, and fintech competition. Research implications – PT. Pegadaian should prioritize credit risk management to sustain ROE and expand performance monitoring to include external macroeconomic factors. Theoretically, the findings suggest that efficiency theory’s predictions may be context-sensitive when applied to collateral-based institutions. This study is limited by its single-institution design, small sample of 18 observations, and exclusion of macroeconomic and structural variables. Originality/value - Provides an exploratory institution-specific analysis of PT. Pegadaian, as state-owned collateral-based lender, contributing evidence that bank-derived determinants of profitability may not behave uniformly in non-bank financial institutions with distinct cost structure and revenue models.